2011
DOI: 10.1111/j.1365-3040.2011.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of young and adult leaves to herbicide 2,4‐dichlorophenoxyacetic acid in pea plants: role of reactive oxygen species

Abstract: In this work the differential response of adult and young leaves from pea (Pisum sativum L.) plants to the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) (23 mm) applied by foliar spraying was investigated. The concentration of 2,4-D (23 mm) and the time of treatment (72 h) were previously optimized in order to visualize its toxic effects on pea plants. Under these conditions, the herbicide induced severe disturbances in mesophyll cells structure and proliferation of vascular tissue in young leaves and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 75 publications
(110 reference statements)
6
96
1
1
Order By: Relevance
“…Plant cell can generate many reactive oxygen species (ROS) in response to stress conditions, such as heavy metal pollution, extreme temperature, drought, saline and herbicides (Pazmiño et al, 2011;Liu et al, 2012;Bhaskaran and Panneerselvam, 2013). If the ROS are not cleared promptly, plasma membranes can be attacked, causing lipid peroxidation and substantial leakage of electrolytes and small organic molecules, damaging the membrane system, causing disorder in various metabolic processes and damage to plant physiological processes (Semane et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Plant cell can generate many reactive oxygen species (ROS) in response to stress conditions, such as heavy metal pollution, extreme temperature, drought, saline and herbicides (Pazmiño et al, 2011;Liu et al, 2012;Bhaskaran and Panneerselvam, 2013). If the ROS are not cleared promptly, plasma membranes can be attacked, causing lipid peroxidation and substantial leakage of electrolytes and small organic molecules, damaging the membrane system, causing disorder in various metabolic processes and damage to plant physiological processes (Semane et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…8 The increase of ROS production induced by 2,4-D is a direct consequence of the activation of specific enzymes such as xanthine oxidoreductase (XOD) involved in ureide metabolism, acyl-CoA oxidase (ACX) involved in fatty acid β-oxidation and jasmonic acid biosynthesis, and lipoxygenase (LOX). 9 NADPH oxidases from the plasma membrane have been considered one of the main sources of ROS induced by auxinic compounds, although in pea plants this activity has been found not to change in response to 2,4-D. 9 ROS are also involved in 2,4-D-induced epinasty by promoting cell expansion and vasculartissue proliferation, 9,10 also acting as signal molecules to induce the cellular response against stress conditions. 6 In addition, these oxidants can participate in the onset of specific gene expression in response to 2,4-D, although the gene network involved in the cell response to 2,4-D governed by ROS has not yet been defined and thus is still under study (RomeroPuertas et al, unpublished results).…”
Section: Role Of Reactive Oxygen Species and No In 24-d Toxicitymentioning
confidence: 99%
“…An overdose of 2,4-D as well as of IAA, activate de novo synthesis of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase, which is a key enzyme in ethylene biosynthesis. 13 However, the role of ET on 2,4-D toxicity is controversial and several authors have demonstrated that it does not participate in 2,4-D-dependent leaf epinasty, 9,14,15 although it can participate in the 2,4-Dinduced plant senescence. 8,9 Another consequence of ET overproduction is the formation of cyanide, an inhibitor of plant enzymes and proteins such as cytochrome-c oxidase, RuBisCo, nitrate/ nitrite reductase, catalase, and peroxidase.…”
Section: 4-d Induced Hormone Imbalancementioning
confidence: 99%
See 2 more Smart Citations